OVERVIEW OF KNOWLEDGE ABOUT FREE SEX AND EARLY MARRIAGE OF TEENS - Rahmawati, Wenny; Retnaningrum, Dwi Norma (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2025)
Data from BKKBN for 2023 shows worrying adolescent sexual behavior in Indonesia. 60% of Indonesian teenagers are involved in sexual relations at the age of 16-17 years. In addition, 20% of teenagers have sex at the age of 19-20 years and 20% even have sex at the age of 14-15 years. This free sexual behavior will trigger an increase in the occurrence of early marriages caused by marriage by accident. Early marriage at the age of less than 19 years will cause various reproductive and psychological health problems in teenagers. This study aims to determine the description of knowledge related to free sex and early marriage in adolescents using a cross-sectional method. As a result, the majority (49.7%) of respondents had poor knowledge about free sex, a small portion (9.2%) had poor knowledge about free sex. Regarding early marriage, the majority (41.6%) of respondents had poor knowledge regarding the concept of early marriage and a small portion (4.3%) had poor knowledge.